18% High‐Efficiency Air‐Processed Perovskite Solar Cells Made in a Humid Atmosphere of 70% RH. Issue 9 (20th July 2017) - Cheng, Yuanhang; Xu, Xiuwen; Xie, Yuemin; Li, Ho‐Wa; Qing, Jian; Ma, Chunqing; Lee, Chun‐Sing; So, Franky; Tsang, Sai‐Wing
Abstract : Despite the advanced progress in power conversion efficiency (PCE), developing air‐processed high‐efficiency perovskite solar cells (PVSCs) for future commercialization is still challenging. Here, we report that besides the general wisdom of the effect of moisture, oxygen in air has a severe impact on the quality of the solution‐deposited perovskite films. Interestingly, as opposed to moisture that induces fast crystallization of PbI2 upon deposition, oxygen exacerbates the wettability of the PbI2 solution on the substrates. We find that simply preheating the substrate and PbI2 solution a fully covered and uniform PbI2 film deposited in air can be obtained. This is possibly due to the increased vapor pressure of the solvent at higher temperatures to reduce the ingress of oxygen and moisture during the PbI2 deposition. Using this simple method, an air‐processed PVSC made under a humid atmosphere of 70% RH has a record PCE of 18.11%. Our work not only reveals the origin of the detrimental effects on perovskite film formation in ambient air, but also provides a simple practical strategy to develop air‐processed high‐efficiency PVSCs for future commercialization. Abstract : 18.11% high‐efficiency air‐processed planar perovskite solar cells (PVSCs) have been fabricated under a humid atmosphere of 70% RH by reducing the detrimental effects of moisture and oxygen in ambient air, using preheating assisted two‐step spin‐coating method.